2015
DOI: 10.1002/lite.201500002
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate oil as a valuable pharmaceutical and nutraceutical

Abstract: Pomegranate oil is the unique edible oil produced from the seed of the pomegranate fruit (Punica granatum L.), which can be extracted by various methods including supercritical CO2, superheated hexane, cold pressing, microwaves and ultrasound. The oil composition of pomegranate seed has received particular attention recently due to its content of antioxidant and anticancer agents, which may be important components for the production of new medicines and cosmetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Studies have shown that CLNAs suppress tumor cell growth by a mechanism that involves lipid peroxidation [ 16 , 45 , 46 ]. Some researchers have also reported that conjugated fatty acids have antioxidant activity and that this could be a possible explanation for their beneficial health effects [ 27 , 47 , 48 ]. According to Yang et al [ 34 ], although the mechanisms of biological activities related to CLNAs are linked to oxidation, controversial results have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that CLNAs suppress tumor cell growth by a mechanism that involves lipid peroxidation [ 16 , 45 , 46 ]. Some researchers have also reported that conjugated fatty acids have antioxidant activity and that this could be a possible explanation for their beneficial health effects [ 27 , 47 , 48 ]. According to Yang et al [ 34 ], although the mechanisms of biological activities related to CLNAs are linked to oxidation, controversial results have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…It is found in high amounts (> 50 %) in pomegranate seed oil (PSO) [ 26 ]. For this reason, PSO has been increasingly investigated as a potent functional food and/or nutraceutical ingredient in foods [ 27 ]. According to Koba et al [ 28 ], because pomegranate abounds in PA its seed oil represents a suitable source for the investigation of the physiological roles of this CLNA isomer.…”
Section: Introductionmentioning
confidence: 99%
“…This fatty acid has been indicated to have positive health effects, such as cholesterol lowering, antidiabetic, anti‐inflammatory, and anticarcinogenic properties . Moreover, pomegranate seed oil (PSO) is rich in other important functional compounds, such as polyphenols, including gallic acid and ellagic acid, phytosterols (β‐sitosterol, campesterol, and stigmasterol) and tocopherols, mainly γ‐tocopherol . Due to its peculiar composition, PSO is today widely used in cosmetic and pharmaceutical products and there are still few applications of this oil as functional ingredient in foods .…”
Section: Introductionmentioning
confidence: 99%
“…The constituents of PSO could mainly be grouped into lipids, tocopherols, and sterols. [38,43,44] However, these components vary from one study to another and Amri et al [39] attributed this fluctuation to genetic variability, extraction process, and maturation stage of pomegranate fruit. The fatty acid compositions estimated in PSO from different countries varied substantially in terms of quantity and types (Table 1).…”
Section: Chemical Compositionsmentioning
confidence: 99%